285. Dose indices in direct digital mammography: Evaluation on phantom and on a patient sample compared with the structured dose report values. (December 2018) - Pozzi, L.; Nocera, P.; Novario, R.
Abstract : Purpose: In DR mammography, comparison of the Entrance Skin Dose (ESD) and the Average Glandular Dose (AGD) data provided by the structured dose report (SR) with the measures performed on phantom and on patient. Methods: Two identical mammography systems, Amulet (Fujifilm), working in AEC with W/Rh spectrum and voltage range of 26–32 kV, were taken into account. For a PMMA phantom (18 × 24 cm 2, thickness of 20–70 mm) and for a sample of 21 patients, both ESD and AGD were estimated. The X-ray output was measured, while Compressed Breast Thickness (CBT), age, tube loading and voltage were taken from the SR. The analysed images are 83, grouped by patient age and CBT. The backscatter factor for the ESD is 1.08. The AGD was estimated according to the "European guidelines for quality assurance in breast cancer screening and diagnosis" (2006 and updates)[1] . In the phantom case, the breast equivalent thickness was considered. In the patient case, the average output of the two systems was used. Results: The table summarises estimated mean, SD and average percentage difference between SR and estimated values for ESD and AGD by patient age and CBT. In the graph, the percentage differences are reported as a function of CBT for both PMMA and patients. In the latter case, the data were separated by age range. Conclusions: Both PMMA and patient ESD from the SR are an overestimation of the calculated value of at least 20% for all the CBT considered. Percentage differences of AGD are comprised within ±15% for CBT greater than 40 mm, while for smaller thicknesses an overestimation results in the range of 15%-25%. The split of the patient AGD curve may come from the mammography systems, which may not consider the patient age in the dose calculation (hypothesis to verify with the systems producer).